Artistic and Aesthetic Formation and Evolution of Architectural and Urban Planning Space - Bulakh, I.V. (Science and Innovation, 2024)
Introduction. The chaotic and random development of urban space is typical for all cities of Ukraine and for the majority of cities of the world. This phenomenon is caused by progressive urbanization, globalization, internationalization, commercialization, and pop culture of the urban planning environment. Problem Statement. The neglect of urban context, regional features of the territories, and historical palimpsest layers of building sites, as well as the domination of material values over intellectual enrichment are the reasons for the lack of artistic and aesthetic idea of the urban environment. Purpose. The purpose of this research is to systematize the existing knowledge on symbolization in the context of the creation of artistic image of urban environment and to define the principles of symbolization. Materials and Methods. Comparative analysis, structural and logical modelling, systematization of research results, literary and informational sources, and experimental design methods. Results. The urban environment is considered a hierarchical multilayer system that gradually integrates 4 (global, macro, local, and micro) levels. The formation of architectural and urban artistic image consists of four stages: the search of analogies, the schematic expression of similarity, the abstraction with the help of allegory, and the creation of a symbol through giving a new content to the sum of abstract ideas. The communicative, transformative, commutative, and metamorphic principles of symbolization have been proposed. Conclusions. Among the segmental postmodern ideas of modern city images, environmental concepts, and scientific directions of the studies of urban formation there is one common thing that is the perception of city as a complex, open, and dynamic system. The city artistic image, while developing and expanding in space and time, covers all the levels of formation of architectural and urban environment, which are interconnected by a variety of images of urban planning, architectural compositions of buildings and structures into a single integrity full of symbolic sense.